11‐Cl‐BBQ, a select modulator of AhR‐regulated transcription, suppresses lung cancer cell growth via activation of p53 and p27Kip1. (22nd December 2022) - Nguyen, Bach D.; Stevens, Brenna L.; Elson, Daniel J.; Finlay, Darren; Gamble, John T.; Kopparapu, Prasad R.; Tanguay, Robyn L.; Buermeyer, Andrew B.; Kerkvliet, Nancy I.; Kolluri, Siva K.
Abstract : Aryl hydrocarbon receptor (AhR) is a ligand‐activated transcription factor and functions as a tumour suppressor in different cancer models. In the present study, we report detailed characterization of 11‐chloro‐7H‐benzimidazo[2, 1‐a]benzo[de]iso‐quinolin‐7‐one (11‐Cl‐BBQ) as a select modulator of AhR‐regulated transcription (SMAhRT) with anti‐cancer actions. Treatment of lung cancer cells with 11‐Cl‐BBQ induced potent and sustained AhR‐dependent anti‐proliferative effects by promoting G1 phase cell cycle arrest. Investigation of 11‐Cl‐BBQ‐induced transcription in H460 cells with or without the AhR expression by RNA‐sequencing revealed activation of p53 signalling. In addition, 11‐Cl‐BBQ suppressed multiple pathways involved in DNA replication and increased expression of cyclin‐dependent kinase inhibitors, including p27 Kip1, in an AhR‐dependent manner. CRISPR/Cas9 knockout of individual genes revealed the requirement for both p53 and p27 Kip1 for the AhR‐mediated anti‐proliferative effects. Our results identify 11‐Cl‐BBQ as a potential lung cancer therapeutic, highlight the feasibility of targeting AhR and provide important mechanistic insights into AhR‐mediated‐anticancer actions. Abstract : 11‐chloro‐7H‐benzimidazo[2, 1‐a]benzo[de]iso‐quinolin‐7‐one (11‐Cl‐BBQ) has been identified as a select modulator of aryl hydrocarbon receptor‐regulated transcription (SMAhRT) with anti‐cancer actions. 11‐Cl‐BBQ promoted potent and sustained AhR‐dependent anti‐proliferative effects in cancer cells by activation of p53 signalling. 11‐Cl‐BBQ induced an AhR‐ and p53‐dependent increase in the senescence‐associated beta galactosidase (SA‐β‐gal), a biomarker for an irreversible cell cycle arrest or senescent phenotype.